Australia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper examines the role that government policy in Australia plays in influencing household saving, both directly through its own saving and the structure of the tax, social security and welfare systems, and indirectly through the influence of the policy environment on factors that affect saving such as economic growth. The determinants of household saving in a sample of 21 OECD (Organization for Economic Cooperation and Development) countries are also investigated, using both cross-section and panel estimation techniques.